Association of angiotensin modulators with the course of idiopathic pulmonary fibrosis - Kreuter, Michael; Lederer, David; Molina-Molina, Maria; Noth, Imre; Valenzuela, Claudia; Frankenstein, Lutz; Weycker, Derek; Atwood, Mark; Kirchgaessler, Klaus-Uwe; Cottin, Vincent (Chest, 2019)
Background - Angiotensin peptides have been implicated in idiopathic pulmonary fibrosis (IPF) pathogenesis. Angiotensin modulators are used to treat arterial hypertension, a frequent comorbidity of IPF. This post hoc analysis evaluated associations of antihypertensive treatments with disease-related outcomes in IPF. - Methods - All patients randomized to placebo (n = 624) in the CAPACITY and ASCEND studies were categorized by antihypertensive treatment at baseline. Outcomes of disease progression (first occurrence of ≥ 10% absolute decline in % predicted FVC, ≥ 50-m decline in 6-min walk distance, or death) and all-cause mortality were assessed over 52 weeks. - Results - At baseline, 111 and 121 patients were receiving an angiotensin-converting enzyme inhibitor (ACEi) or an angiotensin II receptor blocker (ARB), respectively; 392 were receiving neither. In multivariable analyses adjusted for differences in baseline characteristics compared with the non-ACEi/ARB group, ACEi treatment (hazard ratio [HR], 0.6 [95% CI, 0.4-0.9]; P = .026), but not ARB (HR, 0.9 [95% CI, 0.6-1.2]; P = .413), was associated with slower disease progression. Furthermore, the increase in all-cause mortality associated with cardiovascular disease was not observed in the ACEi group (HR, 1.1 [95% CI, 0.5-2.9]; P = .782), which presented a similar percentage of IPF-related mortality as the non-ACEi/ARB group (3.6% vs 3.6%). In contrast, patients in the ARB group had greater risk of all-cause mortality (HR, 2.5 [95% CI, 1.2-5.2]). These observations were validated in a pooled analysis that included patients from the INSPIRE trial. - Conclusions - Prospective clinical trials are needed to evaluate whether angiotensin modulators may be beneficial to clinical outcomes in IPF. - Trial Registry - ClinicalTrials.gov; Nos.: NCT01366209, NCT00287716, NCT00287729, NCT00075998; URL: www.clinicaltrials.gov).
Gesehen am 10.02.2020